End of life care knowledge, perceptions and preference among end stage renal disease patients on haemodialysis in Kuantan - Nur Raziana Rozi (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
The role of end of life care is fundamental in end stage renal disease (ESRD) patients, who are known to have high morbidity and mortality rate despite being on dialysis therapy. It necessitates effective communication via shared decision makings between the nephrologists and patients. Due to the inadequacy of current practice, exploring patients' awareness, values and preferences is essential to improve the gaps in end of life care for ESRD patients. The study is aimed to describe the end of life care knowledge, perceptions and preferences among ESRD patients on haemodialysis in Kuantan, Pahang. It is also aimed to validate the questionnaire on ESRD patients' end of life care knowledge, perceptions, and preferences which was used for subsequent study data collection. This is a cross-sectional study involving a total of 350 patients from 14 outpatient haemodialysis centres in Kuantan. Patients who fulfilled the inclusion criteria were recruited via convenient sampling. Data collection began from March till June 2019. Participants completed the validated questionnaire in a structured, interview-based setting by the researcher or trained interviewers. The validation process involved questionnaire development and pretesting, improving and editing of the questionnaire, redistribution for pilot study and finally, the factor analysis and internal consistency reliability testing. All the results were analysed using IBM SPSS Statistics version 20.0. The validation of questionnaire showed good factor loading of more than 0.4 for all the 41 analysed items. All the cronbach's α values obtained for internal consistency reliability analysis were higher than 0.5, the value set for this study. Thus, the questionnaire was successfully validated. The study demonstrated that majority of the respondents had poor knowledge on the disease and end of life care. However, 70% of the respondents felt that it was important for them to be prepared and plan ahead in the case of death with more patients wanted to die at home as compared to hospital. End of life needs which included symptoms management as well as psychological, social and spiritual support were important to most patients yet they were not adequately incorporated in the clinical care practice. The patients' preferences towards a course of treatment that improves quality of life and relieves pain or discomfort was two times higher than those who opt for treatment that aimed at prolonging life as long as possible. More than half of the patients wanted their end of life care plan regularly reviewed by the nephrologists, however, the discussion rarely took place. This study has been conducted using a successfully validated questionnaire. The reported knowledge among majority of dialysis patients on the end of life care is poor. However, most patients perceive it as important. Yet, only a minority have engaged in the discussion on end of life care choices and preferences with their health team despite their willingness and comfortability to do so. The study findings highlight the gaps between current local clinical practices and patients' preferences in the end of life care.